Using restorative justice to rethink the temporality of transition in Chile - Haan, Marit de (2021)
Assumptions of linear progress and a clean break with the past have long characterised transitional justice interventions. This notion of temporality has increasingly been problematised in transitional justice scholarship and practice. Scholars have argued that a more complex understanding of temporalities is needed that better accommodates the temporal messiness and complexity of transitions, including their ongoingness, multilayeredness and multidirectionality. Existing critiques, however, have not yet resulted in a new conceptual framework for thinking about transitional temporalities. This article builds on insights from the field of restorative justice to develop such a framework. This framework foregrounds longer timelines, multilayered temporalities and temporal ecologies to better reflect reality on the ground and victims’ lived experiences. We argue that restorative justice is a useful starting point to develop such a temporal framework because of its actor-oriented, flexible and interactive nature and proximity to the field of transitional justice. Throughout this article we use the case of Chile to illustrate some of the complex temporal dynamics of transition and to illustrate what a more context-sensitive temporal lens could mean for such cases of un/finished transition